The influence of perceived teacher support on online English learning engagement among Chinese university students: a cross-sectional study on the mediating effects of self-regulation - Yin, Danting; Luo, Lin (Frontiers in Psychology, 2024)
Objectives This study examines the association between perceived teacher support and self-regulation in learning, and their combined relationship with online English learning engagement among university students in China. The objective is to uncover the underlying mechanisms of this relationship, with a particular focus on the role of self-regulation in learning as a mediator. Methods The study involved 1,361 university students from Southwest China, predominantly female (73.84%) with an average age of 18.94 years (SD = 1.07). Refined measurement tools were employed to assess perceived teacher support, online English learning engagement, and self-regulation in learning. Results The findings indicate that components of self-regulation, such as goal setting, environmental structuring, and time management, act as full mediators in the relationship between perceived teacher support and online English learning engagement. Conclusion This research underscores the importance of self-regulation in learning in linking perceived teacher support with online English learning engagement. The insights gained are crucial for enhancing teaching strategies in online English language education.